Control the fate of human umbilical cord mesenchymal stem cells with dual‐enzymatically cross‐linked gelatin hydrogels for potential applications in nerve regeneration. (13th July 2020) - Li, Jinrui; Gao, Feng; Ma, Shanshan; Zhang, Yanting; Zhang, Junni; Guan, Fangxia; Yao, Minghao
Abstract: Stem‐cell‐based therapy is a promising strategy to treat challenging neurological diseases, while its application is hindered primarily by the low viability and uncontrolled differentiation of stem cell. Hydrogel can be properly engineered to share similar characteristics with the target tissue, thus promoting cell viability and directing cell differentiation. In this study, we proposed a new dual‐enzymatically cross‐linked and injectable gelatin hydrogel for regulating survival, proliferation, and differentiation of human umbilical cord mesenchymal stem cells (hUC‐MSCs) in a three‐dimensional matrix. This injectable gelatin hydrogel was formed by oxidative coupling of gelatin–hydroxyphenyl acid conjugates catalyzed by hydrogen horseradish peroxidase (HRP) and choline oxidase (ChOx). Modulus and H2 O2 release can be well controlled by ChOx activity. Results from calcein‐AM/PI staining and Ki67 immunofluorescence tests demonstrated that the survival and proliferation behavior of hUC‐MSCs were highly enhanced in HRP1U ChOx0.25U hydrogel with lower modulus and less H2 O2 release compared with other groups. Attractively, the expression of neuron‐specific markers β‐III tubulin, neurofilament light chain (NFL), and synapsin‐1 was significantly increased in HRP1U ChOx0.25U hydrogel as well. Additionally, in vitro hemolysis test and in vivo HE staining data highlighted the good biocompatibility. Undoubtedly, this injectable gelatin hydrogel's ability to control hUC‐MSCs' fate holds enormous potentials in nervous disorders' therapy and nerve regeneration.